Effect of chemical substituents on the structure of glassy diphenyl polycarbonates - Sulatha, M. S.; Natarajan, Upendra (Journal of Physical Chemistry B, 2011)
Polycarbonates offer a wide variety of physical property behavior that is difficult to predict due to complexities at the molecular scale. Here, the physical structure of amorphous glassy polycarbonates having aliphatic and cycloaliphatic chemical groups is explored through atomistic simulations. The influence of chemical structure on solubility parameter, torsion distributions, radial distribution function, scattering structure factor; orientation distributions of phenylene rings and carbonate groups, and free volume distributions, leading to interchain packing effects, are shown. The effect of the cyclohexyl ring at the isopropylidene carbon as compared to the effect of the methyl groups positioned on the phenylene rings results in a larger reduction in the solubility parameter (delta). The interchain distance estimated for polycarbonates in this work is in the range of 5-5.8 angstrom. The o-methyl groups on the phenylene, rings, as compared to a cyclohexyl ring, lead to higher interchain distances. The highest interchain distance is observed with a trimethylcyclohexylidene group at the isopropylidene carbon. Atomistic simulations reveal two different types of packing arrangement of nearest neighbor chains in the glassy state, one type of which agrees with the NMR experimental data The fundamental insights provided here can be utilized for design of chemical structures for tailored macroscopic properties.